Edukasi Kesehatan Tentang Pencegahan Hipertensi Pada Masyarakat Di Kelurahan Kelayan - Ernawati .; Sri Purwanti Ariani; Nur Nadia (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
The health education program on hypertension prevention in Kelayan Village aimed to improve community knowledge and awareness through counseling, interactive discussions, and educational media. The results showed an increase in participants’ understanding of risk factors and prevention strategies, along with a positive shift toward healthier lifestyle behaviors. The outputs of this program include a scientific article published in a national journal and an educational poster that has obtained intellectual property rights (IPR). The implementation was supported by village authorities and local health workers through the provision of facilities and coordination, although several challenges were encountered, such as limited participant attendance and varying levels of understanding. Future activities will focus on continuous mentoring, strengthening the role of community health cadres, and developing digital-based educational media to promote sustainable behavioral change in the community.